World-Picture Concept Development in Children with Developmental Disabilities by the Method of Visual Modeling - Shcherbakova, A.M. (Autizm i narušenie razvitiâ, 2022)
rial is assimilated easier than verbal. This is especially important for children with mental developmental disorders, since they solve mental problems with the predominant role of external visual means. Visual models, being an accessible form of mediation, are considered as the basis for the development of a child’s mental abilities. The world-picture concept which is improved in children with various types of developmental impairments, including those with autism spectrum disorders (ASD), in comparison with the world-picture concept of normatively developing children, has specific features. We are faced with the problem of the design of psycho-educational work on the development of a world-picture concept in children with ASD, which requires the accumulation of empirical experience. An example is given that illustrates the work of creating of the world-picture concept by a 12-year-old adolescent with ASD, who experiences problems of self-determination and interaction with the outside world, demonstrating patterns of behavior characteristic of ASD. The results of the work are described, the success criteria of which were taken as the ability of a adolescent to visually express a structured model of the world, in which the author can determine his place, as well as a demonstration of readiness to make a choice, accept the new, and not avoid it. The prospects for the further research aimed at the confirming the effectiveness of the technique are discussed, which requires its structured description with the identification of the parameters of the expected positive dynamics of the development with its approbation on a representative sample of children with different types of development. Раскрывается значение картины мира как особого способа ориентации человека в жизни. Обосновывается необходимость овладения ребенком наглядным моделированием для репрезентации картины мира. Подчеркивается, что наглядное моделирование помогает зрительно представлять сложные явления и ситуации и постигать их, так как наглядный материал усваивается легче вербального. Это особенно важно для детей с нарушениями психического развития, поскольку мыслительные задачи решаются ими с преобладающей ролью внешних визуальных средств. Именно наглядные модели, являясь доступной формой опосредования, рассматриваются как основа для развития психических способностей ребенка. Картина мира, формирующаяся у детей с различными вариантами нарушенного развития, в том числе с расстройствами аутистического спектра (РАС), в сравнении с картиной мира нормативно развивающихся детей имеет специфические особенности. Встает задача проектирования психолого-педагогической работы по формированию и развитию картины мира у детей с РАС, для чего необходимо накопление эмпирического опыта. Приводится пример, иллюстрирующий работу по созданию картины мира подростком с РАС 12-ти лет, который испытывает проблемы самоопределения и взаимодействия с окружающим миром, демонстрируя характерные для РАС паттерны поведения. Описаны результаты работы, критериями успешности которой были приняты способность подростка наглядно выразить структурированную модель устроения мира, в которой автор может определить свое место, а также демонстрация готовности совершить выбор, принять новое, а не избегать его. Обсуждаются перспективы дальнейших исследований, направленных на подтверждение эффективности методики, для чего необходимо ее структурированное описание с выделением параметров ожидаемой положительной динамики развития, с апробированием ее на репрезентативной выборке детей с различными вариантами онтогенеза.